Genomic Diversity of Cholera Outbreak Strains in East Malaysia - Lesley Maurice, Bilung; Fuh, Yong Sy; Velnetti, Linang; Adom, Benjamin; Micky, Vincent; Kasing, Apun; Samuel, Lihan; Lin, Chien Su (Universiti Putra Malaysia, 2014)
Thirty one Vibrio cholera isolates recovered from cholera outbreak in Bintulu, Sarawak (Malaysia) were detected with the presence of ctx gene by using specific PCR. These isolates were further characterized and differentiated by using the Enterobacterial Repetitive Intergenic Consensus PCR (ERIC-PCR) and BOX-PCR to determine their genomic fingerprints. The specific PCR result confirmed the identities of 27 isolates out of 31 as pathogenic V. cholerae. The ERIC-PCR generated several genetic profiles consisting of 4-6 bands with sizes in the range of 100 to 600 bp, while the BOX-PCR produced profiles numbering 2-7 bands in the sizes between 200 to 1000 bp. Based on the dendrogram generated from the DNA fingerprinting profiles (ERIC-PCR and BOX-PCR), all of the isolates can be divided into 2 main clusters that is further divided into 2 sub-clusters. The low genetic diversity of the isolates indicated the outbreak of V. cholerae in the study area was due to the contamination from a single or few sources of V. cholerae.